Determinants of Performance in Physical Sciences at Uganda Certificate of Education: A Case Study of Selected Schools in Ntungamo Municipality. - Muhindo, Alex (Kabale University, 2024)
The study assessed the determinants of performance in physical sciences at UCE in selected schools of Ntungamo Municipality, Uganda. The study was guided by two objectives namely: to investigate how learner factors, teacher factors, and school-based factors determine the performance of learners in physical sciences at UCE in Ntungamo municipality and to establish measures that can be put in place to improve the performance of learners in physical sciences at UCE in Ntungamo municipality. The study used a cross-sectional survey research design applying both qualitative and quantitative approaches. From a population of 315 respondents, 190 formed a sample. The questionnaires and interviews were used to collect data. A response rate of 99% was obtained where key findings revealed a significant positive influence of learner factors and school-based factors, while teacher factors had a significant negative influence on the performance of learners in physical science subjects at UCE. Regarding learner factors, it was concluded that changing learners’ attitudes towards physical sciences, improving learners’ interest and their motivation to discuss with friends, consult teachers, and search for more information on the internet would help to improve performance in physical sciences. On teacher factors, there is a need for teachers to be more innovative and try to improvise local materials to teach physical sciences to arouse the interest of the learners, cut down on the costs of buying teaching aids, help the learners to appreciate their local environment in the study of sciences and consequently deepen their understanding of physical sciences in their context. Further, the teachers should also revise their classroom practices in terms of content, context, methodology, and assessment so that they can encourage student participation during content delivery. On school-based factors, it was concluded that there was a need to have well-equipped science laboratories and computer laboratories with internet services to promote the teaching and learning of physical sciences. In addition, proper preparation for examinations needs to be given much attention by exposing learners to a variety of sample examinations. Providing vocational guidance to learners in different fields that are related to physical sciences would improve performance in physical sciences.